High frequency spinal cord stimulation for chronic back and leg pain (2020)
Background: High frequency stimulation (HFS) may provide pain relief without the paresthesias typical of traditional low-frequency Spinal cord stimulation (SCS). Methods: A consecutive single-center series of patients was retrospectively reviewed to evaluate safety and efficacy of HF10 therapy. In this 24-month study, 62 patients with variables pathologies (44 patients with back failure surgery syndrome (FBSS), 18 patients with chronic peripheral neuropathic pain in the lower limbs (NeppL) were included to be treated with HF10. Pain outcomes were compared from preoperative baseline and at the conclusion of each study period. Clinical features, outcomes and complications were reviewed. Results: 62 patients completed this study. All patients had a successful trial before the definitive implantation of a spinal cord stimulator at the low dorsal level. The mean follow-up period was 11 months, ranging from 6 to 24 months. 6 patients showed no change from baseline visual analogue scale (VAS) after permanent implant and 2 had improved during the trial but was aggravated after the permanent implant placement. At 1 month, 63% of implanted HF10 therapy subjects were responders and 77% at 6 months. The average baseline, trial and postoperative Visual Analogue Scale (VAS) was 8.1, 3.6 and 4.2 respectively. When compared to the baseline, the average reduction achieved during the VAS trial was 4.5 points, accounting for a 56% pain reduction. The long-term failure rate was 22%. Conclusions: This study generated preliminary evidence showing improved VAS current pain scores in absence of paresthesias and increase patient satisfaction with HF10 spinal cord stimulation